Protokol Latihan BEST yang Disesuaikan dalam Rehabilitasi Gagal Jantung - Triangto, Kevin; Radi, Basuni; Siswanto, Bambang Budi; Tambunan, Tresia Fransiska Ulianna; Heriansyah, Teuku; Harahap, Alida Rosita; Kekalih, Aria; Ambari, Ade Meidian; Dwiputra, Bambang; Desandri, Dwita Rian; Katsukawa, Hajime; Santoso, Anwar (Jurnal Kardiologi Indonesia, 2024)
Introduction Heart failure with a reduced ejection fraction (HFrEF) significantly contributes to global morbidity and mortality, necessitating effective rehabilitation programs. Exercise-based rehabilitation improves functional capacity and quality of life in HFrEF patients, though responses vary. The tailored BEST (Breathing, Endurance, and Strengthening) exercise protocol addresses both cardiac and extracardiac rehabilitation, benefiting all patients regardless of response status. This study evaluated the protocol's effects on HFrEF patients and classified responses based on VO2max changes. Methods In this etiologic study with prospective cohort design, all participants underwent a three-month cardiac rehabilitation program using the BEST Exercise Protocol. Assessments included the 6-minute walk test (6MWT), short physical performance battery (SPPB), handgrip strength, chest expansion, ultrasonographic measurements, and NT-proBNP levels before and after the intervention, with statistical comparisons made within and between groups. Groupings of responder level will be reliant on 6MWT distance achievement at the end of the program, with ≥6% improvement classified as good responders. Results Out of 107 HFrEF patients (median age 55 years, ejection fraction 29.50±7.34%), 63.56% were good responders and 36.44% were poor responders (<6% improvement). Good responders showed significant improvements in most extracardiac parameters, including a 20% increase in 6MWT distance (470.96±69.21 meters post-rehabilitation), chest expansion, handgrip strength, and SPPB scores (p<0.001 for all). Poor responders also improved in chest expansion, sit-to-stand time, and postural balance, with minor 6MWT gains (407.33±72.50 meters). NT-proBNP levels decreased in both groups but were not statistically significant (p=0.288 and 0.368 for good and poor responders, respectively). Conclusion The tailored BEST Exercise Protocol offers substantial cardiac and extracardiac benefits for HFrEF patients by enhancing functional capacity and muscle strength. Both good and poor responders exhibited significant improvements, indicating the protocol's broad applicability. However, the lack of statistically significant NT-proBNP reduction suggests further studies on cardiac biomarkers are needed. The 6MWT provides accessible rehabilitation insights, though more precise evaluations like Cardiopulmonary Exercise Testing (CPET) can offer clearer insights into cardiopulmonary adaptations.